2006
DOI: 10.1086/498728
|View full text |Cite
|
Sign up to set email alerts
|

First Whole Atmosphere Nighttime Seeing Measurements at Dome C, Antarctica

Abstract: We report site testing results obtained in night-time during the polar autumn and winter at Dome C. These results were collected during the first Concordia winterover by A. Agabi. They are based upon seeing and isoplanatic angle monitoring, as well as in-situ balloon measurements of the refractive index structure constant profiles C 2 n (h). Atmosphere is divided into two regions: (i) a 36 m high surface layer responsible of 87% of the turbulence and (ii) a very stable free atmosphere above with a median seein… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
110
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 6 publications
5
110
0
1
Order By: Relevance
“…In winter (from March to October) this daily wind speed gradient variation disappears, and the gradient remains permanently and much stronger near to the ground. The resulting shears, combined with the very strong temperature gradient in the same layers, are clearly responsible for the optical turbulence observed in the first 30 m (Agabi et al 2006).…”
Section: Optical Turbulence Conditions Study At Dome Cmentioning
confidence: 93%
See 2 more Smart Citations
“…In winter (from March to October) this daily wind speed gradient variation disappears, and the gradient remains permanently and much stronger near to the ground. The resulting shears, combined with the very strong temperature gradient in the same layers, are clearly responsible for the optical turbulence observed in the first 30 m (Agabi et al 2006).…”
Section: Optical Turbulence Conditions Study At Dome Cmentioning
confidence: 93%
“…This is confirmed by the first set of C n 2 balloons equipped with microthermal sensors launched at Dome C during the first over-wintering season (March-August 2005). They show that largest part of the optical turbulence is generally confined in the first 36m (Agabi et al 2006). Probably, such a turbulent inversion layer must be present everywhere on the polar plateau, during all winter, with a thickness that must depend on the katabatic winds and on the penetration in the continent of coastal air streams.…”
Section: Optical Turbulence Conditions Study At Dome Cmentioning
confidence: 99%
See 1 more Smart Citation
“…During the 2006 polar winter a DIMM (Agabi et al 2006) was operating on an other platform, 15 m away from the SSS platform, both at 8 m above ice level. The DIMM measures the seeing continuously and it allows a direct comparison with SSS seeing measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, the Astro-Concordia station was first opened for winterover during which two DIMMs were set up and 40 meteorological balloons, instrumented for C 2 N (h) and V(h) profiling, were launched. Again, it became obvious that most of the turbulence was generated within the surface layer (Agabi et al 2006), as was found at the South Pole, but with a depth of only 30 m.…”
Section: Introductionmentioning
confidence: 89%